Physical mapping of the anopheles (Nyssorhynchus) darlingi genomic scaffolds - Rafael, Míriam Silva; Bridi, Letícia Cegatti; Sharakhov, Igor V.; Marinotti, Osvaldo; Sharakhova, Maria V.; Timoshevskiy, Vladimir A.; Guimarães-Marques, Giselle Moura; Santos, Valéria Silva; da Silva, Carlos Gustavo Nunes; Astolfi-Filho, Spártaco A.T.; Tadei, Wanderli Pedro (Insects, 2021)
The genome assembly of Anopheles darlingi consists of 2221 scaffolds (N50 = 115,072 bp) and has a size spanning 136.94 Mbp. This assembly represents one of the smallest genomes among Anopheles species. Anopheles darlingi genomic DNA fragments of ~37 Kb were cloned, end-sequenced, and used as probes for fluorescence in situ hybridization (FISH) with salivary gland polytene chromosomes. In total, we mapped nine DNA probes to scaffolds and autosomal arms. Comparative analysis of the An. darlingi scaffolds with homologous sequences of the Anopheles albimanus and Anopheles gambiae genomes identified chromosomal rearrangements among these species. Our results confirmed that physical mapping is a useful tool for anchoring genome assemblies to mosquito chromosomes.
Keywords: in situ hybridization; genomics and cytogenetics; synteny; polytene chromosome